Inflammatory eye reactions with bisphosphonates and other osteoporosis medications: what are the risks?. (February 2015) - Clark, Emma M.; Durup, Darshana
Inflammatory eye reactions (IERs) are rare but have been associated with medications to treat osteoporosis. The aim of this review is to summarize the current literature on the association between IERs and specific medications to treat osteoporosis (bisphosphonates, selective estrogen receptor modulators, strontium, denosumab and teriparatide). We cover the known epidemiology, potential pathogenic mechanisms and a resume of unanswered questions. Briefly, this review highlights that none of the existing randomized clinical trials were powered to identify these rare adverse events, and the majority of the information available is from spontaneous case reports and case series reporting associations between bisphosphonates and IERs. No case reports describe IERs after other anti-osteoporosis medications. Importantly, some case reports describe recurrence of the IER after affected patients were rechallenged with the same or another bisphosphonate, and that no reported cases resolved without discontinuation of the bisphosphonate. However, three large population-based cohort studies have shown conflicting results between osteoporosis treatments and IERs, but overall these studies suggest that IERs may actually be part of underlying inflammatory disease processes that also cause osteoporosis, rather than due to the medications used to treat osteoporosis themselves. There are no clear pathogenic mechanisms for how bisphosphonates could potentially cause IERs. However, the drug is secreted into the tears by the lacrimal gland and could cause irritation to the mucous membranes with subsequent release of inflammatory mediators, similar to the systemic response typically seen after infusion of bisphosphonates. However, in summary it is still not known whether there is a true causal association between bisphosphonates or other anti-osteoporosis medications and IERs, or whether it is confounding by indication and is actually due to underlying inflammatory diseases that cause both osteoporosis and IERs.